Coordination tunes the activity and selectivity of the nitrogen reduction reaction on single-atom iron catalysts: a computational study - Jiao, Dongxu; Liu, Yuejie; Cai, Qinghai; Zhao, Jingxiang (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Tuning the electronic structure of a single-atom catalyst (SAC) by controlling its coordination has been recently shown to be a rather promising strategy for further improving its catalytic performance in some electrochemical reactions. Herein, by means of density functional theory (DFT) computations, the impacts of the coordination structure of an Fe–N–C catalyst on its catalytic activity toward the nitrogen reduction reaction (NRR) were explored. Our results revealed that the NRR activity on the central Fe atom can be greatly improved by its coordination with a boron (B) dopant. In particular, the computed limiting potential of the NRR on Fe–B 2 N 2 is −0.65 V, which is the lowest among all B doped Fe–N–C catalysts, suggesting its high NRR catalytic activity. Interestingly, the introduction of B coordination can effectively modulate the interaction of the single Fe atom with the N 2 H* species, thus improving its NRR catalytic performance. In addition, Fe–B 2 N 2 exhibits high NRR selectivity by effectively suppressing the competing hydrogen evolution reaction (HER) both thermodynamically and kinetically. Therefore, the single Fe catalyst with N and B dual coordination can be utilized as a promising NRR electrocatalyst, which not only highlights the significant effect of local coordination on catalytic activity and selectivity for the NRR, but also provides a new opportunity to further develop more advanced single-atom catalysts for ammonia synthesis.